Humour or humiliation? When classroom banter becomes irresponsible sledging in upper-primary school contexts. Issue 3 (4th May 2021) - Penelope Wardman, Natasha
ABSTRACT: In a global context where children are increasingly exposed to hostile humour in cartoons like Adventure Time and Spongebob Squarepants, it is not surprising that we see this play out in school settings. More concerning, however, is how teachers can misuse their position of power to wield such forms of humour against students who dare to question their authority. This paper draws on ethnographic data from three regional Australian primary schools to address how the performative violence of hostile 'humour' is enacted by male teachers at the expense of less violent and more 'responsible' alternatives. I employ gender-based theories and literature to argue that hostile humour is another mechanism through which hierarchies of hegemonic masculinity are maintained and 'the top dog' (or teacher) is positioned to have the last laugh.